Phytosynthesis of intracellular and extracellular gold nanoparticles by living peanut plant (Arachis hypogaea L.) - Raju, Dugyala; Mehta, Urmil J.; Ahmad, Absar (Biotechnology and Applied Biochemistry, 2012)
Inorganic nanomaterials of different chemical compositions are conventionally synthesized under harsh environments such as extremes of temperature, pressure, and pH. Moreover, these methods are eco-unfriendly and cumbersome, yield bigger particles, and agglomerate because of not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions, namely room temperature, atmospheric pressure, and physiological pH. These methods are reliable, eco-friendly, and cheap. In this paper, we report for the first time the extracellular and intracellular synthesis of gold nanoparticles (GNPs) using living peanut seedlings. The formed GNPs were highly stable in solution and inside the plant tissue. Transmission electron microscopy revealed that extracellular GNPs distributions were in the form of monodispersed nanoparticles. The nanoparticles ranged from 4 to 6 nm in size. The intercellular nanoparticles were of oval shape and size ranged from 5 to 50 nm. Both extracellular and intracellular nanoparticles were further characterized by standard techniques. The formed GNPs inside the plant tissue were estimated by inductively coupled plasma spectrometry. This opens up an exciting possibility of a plant-based nanoparticle synthesis strategy, wherein the nanoparticles may be entrapped in the biomass in the form of a film or produced in the solution, both of which have interesting applications.
Keywords: cells; extracellular; living plant; Peanut; root; TEM

Biogenic green synthesis of monodispersed gum kondagogu (Cochlospermum gossypium) iron nanocomposite material and its application in germination and growth of mung bean (Vigna radiata) as a plant model - Raju, Dugyala; Mehta, Urmil J.; Beedu, Sashidhar Rao (IET Nanobiotechnology, 2016)
An eco-friendly green and one-pot synthesis of highly monodispersed iron (Fe) nanoparticles (NPs) by using a natural biopolymer, gum kondagogu (GK) as reducing and capping agent is proposed. The NPs synthesised were characterised by ultra-violet-visible spectroscopy, transmission electron microscopy, scanning electron microscopy and X-ray diffraction. As the concentration of gum and time increases, the intensity of NPs formation increased. The NPs were highly monodispersed with uniform circular shapes of 2-6 nm in size. The formed NPs were crystalline in nature which was confirmed by diffraction analysis. The conversion ratio of Fe ionic form to NPs was 21% which was quantified by inductively coupled plasma mass spectroscopy (ICP-MS). Fe is essential for plant growth and development. A study was conducted to examine the effect of these NPs on the growth of mung bean (Vigna radiata). The radical length and biomass was increased in seeds exposed to Fe NPs than the ions. The uptake of Fe NPs by the sprouts was also quantified by ICP-MS, in which Fe was more in mung bean seeds exposed to NPs. The -amylase activity was increased in the seeds exposed to NPs. The observed increase in the biomass by Fe NPs and seed germination may facilitate its application in the agriculture as an important cost-effective method for plant growth.
Keywords: alpha-amylase activity; Biogenic green synthesis; biological techniques; Biomass; Cochlospermum gossypium; diffraction analysis; enzymes; Fe; gum concentration; high-monodispersed iron nanoparticles; inductively coupled plasma mass spectroscopy; ionic-to-nanoparticle iron conversion ratio; iron; monodispersed gum kondagogu; monodispersed gum kondagogu iron nanocomposite material; mung bean germination; mung bean growth; Nanobiotechnology; Nanocomposites; nanoparticle formation; Nanoparticles; natural biopolymer; plant growth; plant model; scanning electron microscopy; size 2 nm to 6 nm; transmission electron microscopy; ultraviolet spectra; ultraviolet-visible spectroscopy; Vigna radiata; visible spectra; X-ray diffraction